Electrochemical Hydrodimerization of Furfural in Organic Media as an Efficient Route to Jet Fuel Precursor. Issue 2 (27th December 2022) - Temnikova, Maria; Medvedev, Jury; Medvedeva, Xenia; Delva, Nyhenflore H.; Khairullina, Evgeniia; Krivoshapkina, Elena; Klinkova, Anna
Abstract: Upgrading biomass‐derived compounds to value‐added products, especially fuels, represents a green route alternative to fossil fuels energy sources. Here, we report an efficient electrosynthesis of a jet fuel precursor hydrofuroin from furfural, which is one of the most valuable compounds derived from biomass. Despite the high value of this process, few studies have been focused on the development of synthetic strategies for electrocatalytic hydrodimerization of furfural to hydrofuroin. In this work, we systematically examine how operating parameters, including the electrolyte, applied potential, furfural concentration, and catalyst nature affect the efficiency of hydrofuroin electrosynthesis in organic media. We show that under the optimized conditions, the electrosynthesis can be carried out in a simple undivided cell with a high faradaic efficiency (up to 74 %) and an excellent hydrofuroin yield (up to 100 %). Abstract : Taking off with hydrofuroin : An efficient strategy for the electrosynthesis of hydrofuroin – a jet fuel precursor – from biomass‐derived furfural is reported. We show that hydrofuroin can be synthesized in organic media in a simple undivided cell with a high faradaic efficiency (up to 74 %) and an excellent yield (up to 100 %).